A formação de professores formadores do Cefapro-MT: desenvolvimento e identidade profissional - Oliveira, Sílvia Matsuoka de (2015)
The objective of this research was to investigate the process of professional development and the construction of identity of the Trainer-professor (TP), because his important role as the implementer of the Public Policy of Continued Education of Teachers of the State of Mato Grosso, in the Centres for the Education and Updating of Basic Education Professionals (Cefapro). In this context the training policy, the trainer-professors is responsible for monitoring and advising the project of continuing education for schools in the public school system, named Educator's Room (ER). The conception of continuous formation is understood by the collaborative perspective, valuing the school as locus of teacher education, the formative space for collective reflection of pedagogical practice. The research used a qualitative approach, with various methodological procedures for data collection as: public policy documents of formation of Mato Grosso, survey with questionnaires for teachers trainers of 15 Cefapros, memorials of formation of PFs, focus group with PFs and with school teachers and interview with training managers of SUFP. The subjects of the research were the Cefapro polo TPs of Rondonópolis-MT. The top authors who subsidized the studies were: Carlos Marcelo Garcia (1999), Denise Vaillant and Carlos Marcelo (2012), Francisco Imbernón (2009) and Antonio Nóvoa (2009) about the professional development, continuing education of teachers, training of trainer; Bernadette Angelina Gatti (2007) and Claude Dubar (2005) about the identity construction of TP. For the treatment of the data was used to analysis of prose (ANDRÉ, 1983) and the concepts of exotopia and otherness of Mikhail Bakthin. The research considered the training of TP, intrinsically linked to the training of teachers, both work in the same context formation, continuous formation developed at school, by the Educator's Room design. It was possible to analyze that the professional development of the TP the Cefapro happens, mainly, dialogical relations between TP and teacher at the school, when the trainer plays its mediator role in the monitoring of the ER, and yet, between the trainer and his peers, in the Trainer's Room, when reflected collectively on their role. The data showed that the Constitution of identity of TP in the midst of the contradictions of its function, since, now must implement the collaborative culture in continuous formation of teachers, according to education policy, now must perform the external programs offered by SEDUC-MT, in partnership with the Ministry of Education. Such programs are specific trainings, contrary to the concept of continuing education offered by own SEDUC-MT. It´s indispensable closer look at its Constitution of identity of the TP and for his professional development, given the importance for his role